BUTAPAS: Inovasi Media Pembelajaran Kontekstual Budaya Palembang Pada Materi Keberagaman Budaya Indonesia di Sekolah Dasar - Wiwin Ulnisah; Tika Dwi Nopriyanti; Laili Rosita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Science is one of the independent curriculum learning in elementary school. The science learning process in grade IV of SD Negeri 1 Kaliberau found several problems. Based on the results of observations made that teachers have not used science learning media. The definition aims to develop valid and practical BUTAPAS learning media in grade IV. Calculating using the ADDIE learning model (Analysis, Design, Development, Implementation and Evaluation). So that the results of the bitterness study were obtained with an average score of 98% media experts 100% language experts and 99% material experts have the criteria "very valid". Furthermore, the practicality of the product carried out on the teacher response questionnaire with an average of 90% and a small group questionnaire 91.2% with the criteria "very practical" to use. Furthermore, the results of the product effectiveness test through student ability tests with schools 95% with the category "very effective". It can be concluded that the BUTAPAS learning media in grade IV is stated to be the most practical and effective to use the word developed during teaching and learning activities in grade IV of elementary school.